EFFECTIVE TEMPERATURE AND RADIAL VELOCITY OF THE SMALL AMPLITUDE CEPHEID POLARIS (alpha UMi) IN 2015 - Usenko, I. A.; Kovtyukh, V. V.; Miroshnichenko, A. S.; Danford, S. (Одеські астрономічні публікації, 2016)
We present the results of an analysis of 21 spectra of alpha UMi (Polaris) obtained in September – December 2015. Frequency analysis shows an increase of the pulsation period up to 8.6 min in comparison to the 2007 observational set. The radial velocity amplitude comes to 4.16 kms-1, and it approximately twice the one found in 2007. The average Teff = 6017 K, and it is close to the value determined for the 2001–2004 set. Therefore Polaris moves to the red edge of the Cepheid instability strip (CIS).